Analisis Motivasi Belajar Siswa terhadap Pengenalan Algoritma dan Pemrograman pada Kurikulum Merdeka - Widiadnyana, Putu; Liandana, Made; Dwipayana, Ida Bagus Brahmanta (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Informatics subjects with algorithm and programming material are new materials taught in Junior High School in the Merdeka Curriculum. This study aims to analyze the influence of learning motivation from student learning readiness on the application of material in schools. In this study using scratch applications with Arduino as a medium for applying learning. The type of research used in this study is associative research with quantitative methods. The study population was grading VII students with a sample of 23 people. The type of research instrument is a questionnaire that is analyzed using the SmartPLS 3.0 program-assisted path analysis. The research results obtained, namely physical readiness, mental readiness, and learning completeness, did not have a significant enough effect because students already had them; only basic knowledge had an effect because students did not know about algorithms and programming material